Learning strategies, self-esteem and gender in first year university students. - Benjamin, Faheema (My University, 2009)
The aim of the research study is firstly to examine the relationship between self-esteem and learning strategies amongst first year university students. From this the investigator aimed to discern whether there is a link between cognitive and affective factors in student learning as has been widely accepted in pedagogical studies. Secondly, the difference in self-esteem levels in relation to gender and year of study were also examined. Thirdly, the differences in self-esteem and learning strategies in relation to year of study were investigated. The rationale for the investigations in this study stems from the fact that first year university students are seen to be at a major life transition that brings with it challenges on an affective (self-esteem) and cognitive (learning strategies) level. The sample of the study consisted of 197 participants gathered from the University of the Witwatersrand. The instruments utilised were the Rosenberg Self-esteem Scale (1965), the Learning and Study Strategies Inventory- LASSI (Weinstein, 1987) and a brief Student Demographic Survey to gain information such as the students gender and year of study. Findings indicated that there is a relationship between self-esteem and the motivation to learn- one of the components of the LASSI. However, contrary to many other findings, no cognitive-affective link was evident. Furthermore, males and females appeared to show difference in the study aids learning strategy as well as in self-esteem levels, where females proved to have more positive self-esteem levels than the males. Year of study lastly, also proved to have an influence in student self-esteem levels.
Keywords: Learning strategies; Self-esteem; Gender; First year university students